An Epithelial Myoepithelial Carcinoma in Parotid Gland - Etit, Demet; Özdemir, İsmail; Ermete, Murat; Vidinli, Berna (Fırat University, 2007)
Epithelial myoepithelial carcinoma (EMEC) is a tumor composed of variable proportions of two cell types that typically form duct like structures. It is predominantly tumor of the parotid gland. This rare neplasm represents 1% of all salivary gland tumors. EMECs are solitary, well-circumscribed, firm masses measuring between 2 cm and 8 cm in greatest dimension. Surgical excision with disease free margins is the treatment of choice. A-67 year-old male patient was presented with a painless mass on the right preauricular region. The mass had a cystic component on the ultrasound. Pathologic examination showed a uniform pattern of ductular epithelium surrounded by clear cells of myoepithelial origin. It was reported as EMEC. There was no recurrence a twenty month follow up.©2007, Firat University, Medical Faculty

Epitelyal miyoepitelyal karsinom değişen oranlarda 2 farklı hücre tipinin, tipik olarak duktus benzeri yapılar oluşturduğu bir tümördür. Başlıca parotis bezinde görülür. Tüm tükrük bezi tümörlerinin %1'ini temsil eder. Tekil, iyi sınırlı, sert, çapı 2 cm ve 8 cm arasındadır. Salim cerrahi sınırlarla kitle eksizyonu seçkin tedavi yöntemidir. 67 yaşında erkek hasta, sağ preauriküler bölgede ağrısız kitle yakınmasıyla başvurdu. Ultrasonografide kitlenin kistik komponenti mevcuttu. Patolojik incelemede miyoepiteliyal kökenli berrak hücrelerin çevrelediği uniform duktuler epitelyal görünüm izlendi. Olgu epitelyal miyoepitelyal karsinom olarak rapor edilmiş olup 20 aylık takipte rekürrens olmadı. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Parotis Bezinde Epitelyal Miyoepitelyal Karsinom